1986
DOI: 10.1111/j.1398-9995.1986.tb00287.x
|View full text |Cite
|
Sign up to set email alerts
|

Errors in Inhalation Technique and Efficiency in Inhaler Use in Asthmatic Children

Abstract: 256 asthmatic children receiving regular inhalation therapy demonstrated how they used their inhalers. Pulmonary function measurements (PFM) were made before and after the demonstrations, and errors in technique were recorded. 242 children had reversible airway obstruction on the day of study. In only 109 (45%) did the inhalation result in an increase in FEV1 greater than or equal to 15% (efficient technique). An efficient inhalation technique was found in 46% of children who demonstrated a pressurized aerosol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(79 citation statements)
references
References 6 publications
1
76
0
2
Order By: Relevance
“…Most of the difficulties are related to problems with correct coordination of actuation and inhalation -either inhaling too late or too early in relation to the actuation (Table 1). 11,12,26,27 Moreover, cessation of inhalation when the aerosol particles reach the soft palate (the cold Freon effect) or actuation of the aerosol into the mouth followed by inhalation through the nose is common. 11,28 Breath-holding is normally recommended after the inhalation, but the clinical importance of breath-holding has not been documented in children.…”
Section: Common Problems That Children Have In Using Their Inhalers Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the difficulties are related to problems with correct coordination of actuation and inhalation -either inhaling too late or too early in relation to the actuation (Table 1). 11,12,26,27 Moreover, cessation of inhalation when the aerosol particles reach the soft palate (the cold Freon effect) or actuation of the aerosol into the mouth followed by inhalation through the nose is common. 11,28 Breath-holding is normally recommended after the inhalation, but the clinical importance of breath-holding has not been documented in children.…”
Section: Common Problems That Children Have In Using Their Inhalers Cmentioning
confidence: 99%
“…4 In contrast, several studies have demonstrated that large numbers of patients do not use their inhalers correctly and consequently gain little or no therapeutic benefit from the prescribed treatment. [5][6][7][8][9][10][11][12] Therefore, the focus of inhalation therapy should probably be redirected from a main emphasis on in vitro characterisation to assessments of which inhalers are easiest to use correctly by various groups of patients. Due to the heterogeneity of patients no single inhaler will satisfy the needs of all.…”
Section: Why Inhaled Therapy?mentioning
confidence: 99%
“…1 Incorrect and improper inhaler use is a significant problem for both asthma and COPD management because it may result in diminished therapeutic effect, leading to poor control of symptoms and lacunae in management of these diseases. [8][9][10][11][12] Moreover, the notion of complexity of inhaled therapy may lead to discontinuation of treatment, further impairing the achievement of disease control. 13 In fact, Santus et al found that 18% of patients stopped inhaled therapy spontaneously, mainly due to the complexity of treatment, despite a reported suitable medical explanation.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, both children and adults with asthma experience the same problems when using their pMDIs. However, these problems are more pronounced in children, with a greater number of errors seen in those aged under 6 years [10]. Consequently, less than 50% of those children would get the desired therapeutic outcome of their inhaled therapy [3].…”
Section: Introductionmentioning
confidence: 99%